A 4000-year record of hydrologic variability from the Olympic Mountains, Washington, USA. (August 2019) - Smith, Stephen G; Wegmann, Karl W; Leithold, Elana L; Bohnenstiehl, Delwayne R
Sedimentological and geochemical analyses of gravity and piston cores retrieved from Lake Quinault, Washington, reveal an ~4000-year flood-dominated depositional record. Individual flood event layers are identified by combining core stratigraphy, sedimentology, and the ratio of incoherent to coherently scattered x-ray radiation ( inc/coh ) from µXRF (x-ray fluorescence) core scans. The inc/coh time series is used as a proxy for sediment grain size and, in combination with radiocarbon-anchored core age–depth models, enables the reconstruction of late-Holocene hydrologic variability for the Quinault River catchment. Decadal to centennial variability in inc/coh is interpreted to reflect trends in ocean-atmosphere teleconnections favorable for the formation of land-falling atmospheric rivers along the Pacific Ocean flank of the Olympic Mountains. Such processes likely modulate the rate of flooding and may explain notable increases in the frequency of flood event layers observed during the periods 2350–2450 cal. yr BP and the most recent century (AD 1910–2010). Understanding past hydrologic variability has important implications for the landscape and ecosystem response of Olympic Mountain catchments to future climate warming.